The Triangulation Method Using for the Distance to the Object Measurement in a Collaborative Robot Workspace - Yevsieiev, V.; Maksymova, S.; Gurin, D.; Ahmad Alkhalaileh (SYNAPSES: Insights Across the Disciplines, 2024)
The article examines the triangulation method for accurately measuring the distance to objects in a Collaborative Robot Workspace. The effectiveness of using HC SR04 ultrasonic sensors is analyzed, one of which has a blocked TRIG pin, which allows you to focus on receiving reflected signals to calculate the distance. The results of the experiments demonstrate the high accuracy of the measurements, as well as the speed of the system's response to changes in the position of the object. The importance of this approach for improving robotic systems within the concept of Industry 5.0 is highlighted.
Keywords: Triangulation; Collaborative Robot; Ultrasonic Sensors; Distance Measurement; Industry 5.0